A numerical analysis of the resistance and stiffness of the aluminium and concrete composite beam = Analiza numeryczna nośności i sztywności belki zespolonej aluminiowo - betonowej - Polus, Łukasz; Szumigała, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper a numerical analysis of the resistance and stiffness of the aluminium and concrete composite beam is presented. Composite aluminium and concrete structures are quite new and they have not been thoroughly tested. Composite structures have a lot of advantages.
Keywords: belka zespolona; belka betonowo-aluminiowa; analiza numeryczna; aluminium and concrete beam; composite beam; numerical analysis